SERVICE QUALITY OF DIAGNOSTIC FINE NEEDLE ASPIRATION CYTOLOGY IN A TERTIARY CARE HOSPITAL OF LAHORE (PROCESS MEASURE AS PATIENT’S PERSPECTIVE) - Rizvi, Zainab; Usmani, Rabia Arshed; Rizvi, Amna; Wazir, Salim; Zahra, Taskeen; Rasool, Hafza (Journal of Ayub Medical College Abbottabad, 2017)
Background: Quality of any service is the most important aspect for the manufacturer as well as the consumer. The primary objective of any nation’s health system is to provide supreme quality health care services to its patients. The objective of this study was to assess the quality of diagnostic fine needle aspiration cytology service in a tertiary care hospital. As Patient’s perspectives provide valuable information on quality of process, therefore, patient’s perception in terms of satisfaction with the service was measured. Methods: In this cross sectional analytical study, 291 patients undergoing fine needle aspiration cytology in Mayo Hospital were selected by systematic sampling technique. Information regarding satisfaction of patients with four dimensions of service quality process, namely procedure, sterilization, conduct and competency of doctor was collected through interview on questionnaire. The questionnaire was developed on SERVQUAL model, a measurement tool, for quality assessment of services provided to patients. All items were assessed on 2- point likert scale (0=dissatisfied, 1=satisfied). Frequencies and percentages of satisfied and dissatisfied patients were recorded for each item and all items in each dimension were scored. If the percentage of sum of all item scores of a dimension was ‰¥60, the dimension was ’˜good quality’. Whereas <60% was ’˜poor quality’ dimension. Data was analysed using epi-info-3.5.1. Fisher test was applied to check statistical significance. (p-value <0.05) Results: Out of the 4 dimensions of service quality process, Procedure (48.8%), Sterilization (51.5%) and practitioner conduct (50.9%) were perceived as ’˜poor’ by the patients. Only practitioner competency (67.4%) was perceived as ’˜good’. Comparison of dimensions of service quality scoring with overall level of patient satisfaction revealed that all 4 dimensions were significantly related to patient dissatisfaction (p<.05) Conclusion: The study suggests that service quality of therapeutic and diagnostic procedures in public hospitals should be routinely monitored from the patients’ point of view as most aspects of service quality in public hospitals of Pakistan, require improvements. In this manner patient’s satisfaction regarding use of services in public hospitalscan be made better. Keywords: FNAC; SERVQUAL; Service quality measurement instrument; Patient perspective